2020
DOI: 10.1111/eje.12576
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of CAD/CAM technology: A self‐assessment tool for preclinical waxing exercise

Abstract: Introduction This study assessed the utility of CAD/CAM technology as a self‐assessment tool for preclinical waxing compared to traditional student self‐assessment to evaluate preclinical work. Material and Methods Thirty‐seven students completed the wax‐up of the maxillary left central incisor with the goal of recreating original anatomy and completed a traditional self‐assessment. The original, unreduced cast and waxings were scanned with an intraoral scanner (E4D, Planmeca). Using CAD/CAM software (Compare,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…and Chiang et al. showed that students agreed that the use of CAD/CAM in preclinical dentistry was useful and supported the self‐assessment skills of students in preclinical dentistry 14,26 . In addition, Wolgin et al.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…and Chiang et al. showed that students agreed that the use of CAD/CAM in preclinical dentistry was useful and supported the self‐assessment skills of students in preclinical dentistry 14,26 . In addition, Wolgin et al.…”
Section: Discussionmentioning
confidence: 96%
“…Studies by Park et al and Chiang et al showed that students agreed that the use of CAD/CAM in preclinical dentistry was useful and supported the self-assessment skills of students in preclinical dentistry. 14,26 In addition, Wolgin et 1 Answers ranged from 1 = disagree strongly, 2 = disagree, 3 = neither disagree nor agree, 4 = agree to 5 = agree strongly. .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technology is not limited to abutment preparation in preclinical prosthodontic courses. Chiang et al 26 utilized similar technology to help students' self-assessment in a dental anatomy wax-up exercise. In this study, thirty-seven students completed the waxup of the maxillary left central incisor and traditional self-assessment.…”
Section: Cad/cam Dentistry Technology Applications In Dental Educationmentioning
confidence: 99%